Harold and Maude - Islam, Yusuf 1948- (The Criterion collection, 2012)
Countercultural director Hal Ashby tells the story of the emotional and romantic bond between a death-obsessed young man from a wealthy family and a devil-may-care, bohemian octogenarian. Equal parts gallows humor and romantic innocence, Harold and Maude dissolves the line between darkness and light along with the ones that separate people by class, gender, and age. The cult classic of its era, featuring indelible performances and a soundtrack by Cat Stevens